In vivo formation of H(2)O(2) in red cells during exposure to hyperoxia - Johnson, William P. (1972)
Chow-fed and tocopherol-deficient mice were given aminotriazole (AT), exposed to 100% O(2) at 60 pounds per square inch absolute for 1 hr (OHP), and red blood cells were assayed for catalase activity and lipid peroxide levels. A decrease of catalase activity (CA) in the presence of AT can be taken as evidence of excess formation or accumulation of H(2)O(2). No differences of CA were observed among chow-fed mice, with or without AT and/or OHP. Tocopherol-deficient mice with AT had lower CA (0.174±0.040) than chow-fed mice with AT (0.225±0.028) P < 0.01. Tocopherol-deficient mice with AT exposed to OHP had even lower CA, 0.137±0.024, P < 0.01. The data are consistent with the hypothesis that H(2)O(2) is formed or accumulated in excess in red cells of tocopherol-deficient mice, an effect that is enhanced in the presence of hyperoxia. They imply that tocopherol plays a role in the detoxification of H(2)O(2).